A C-terminal ataxin-2 disordered region promotes Huntingtin protein aggregation and neurodegeneration in Drosophila models of Huntington's disease. Issue 12 (9th October 2021) - Huelsmeier, Joern; Walker, Emily; Bakthavachalu, Baskar; Ramaswami, Mani
Abstract: The Ataxin-2 (Atx2) protein contributes to the progression of neurodegenerative phenotypes in animal models of amyotrophic lateral sclerosis (ALS), type 2 spinocerebellar ataxia (SCA-2), Parkinson's disease, and Huntington's disease (HD). However, because the Atx2 protein contains multiple separable activities, deeper understanding requires experiments to address the exact mechanisms by which Atx2 modulates neurodegeneration (ND) progression. Recent work on two ALS models, C9ORF72 and FUS, in Drosophila has shown that a C-terminal intrinsically disordered region (cIDR) of Atx2 protein, required for assembly of ribonucleoprotein (RNP) granules, is essential for the progression of neurodegenerative phenotypes as well as for accumulation of protein inclusions associated with these ALS models. Here, we show that the Atx2-cIDR also similarly contributes to the progression of degenerative phenotypes and accumulation of Huntingtin protein aggregates in Drosophila models of HD. Because Huntingtin is not an established component of RNP granules, these observations support a recently hypothesized, unexpected protein-handling function for RNP granules, which could contribute to the progression of Huntington's disease and, potentially, other proteinopathies.